All-solid-state battery and preparation method thereof
By using specific dispersant in the electrode layer and solid electrolyte layer of an all-solid state battery, the dispersant-containing layer is formed, and the problem of insufficient dispersibility of solid electrolytes is solved, and the ion conductivity and cyclic properties of the battery are improved.
Patent Information
- Application Number
- CN202080106530.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-10-23
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-10-23
AI Technical Summary
In all-solid state batteries, the dispersibility of the solid electrolyte is insufficient, which affects the formation of ion conduction paths and the cyclic properties of the battery.
The dispersibility of the solid electrolyte is improved by using a dispersant having a specific amine value and a weight average molecular weight in the cathode layer, the anode layer and the solid electrolyte layer.
The dispersibility of solid electrolytes is improved, the ion conductivity and the cyclic properties of the battery are improved, and the performance of all-solid state batteries is enhanced.
Smart Images

Figure CN116368634B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to all-solid-state batteries and methods for making the same. Background Art
[0002] An all-solid-state battery is a battery including a solid electrolyte layer between a cathode layer and an anode layer, and has the advantage that its protection is easier to simplify compared to a liquid-based battery having a liquid electrolyte including a flammable organic solvent. Carbon materials are used as conductive materials for cathode layers and anode layers in all-solid-state batteries in some cases, and dispersants that improve the dispersibility of carbon materials are known. For example, Patent Document 1 discloses a dispersant for carbon materials including a copolymer containing nitrogen atoms.
[0003] In addition, although it is not an all-solid-state battery technology, Patent Document 2 discloses a dispersant including carboxylic acid and amine. Patent Document 2 also discloses the removal of deposited materials formed in the engine by using a dispersant. In addition, although Patent Document 2 is not an all-solid-state battery technology, Patent Document 3 discloses an adhesive composition for lithium-ion secondary battery electrodes, which includes a water-soluble polymer X (having a liquid electrolyte swelling degree of less than 120 mass %), an amphoteric dispersant Y and a solvent.
[0004] Reference List
[0005] Patent Literature
[0006] PTL 1: Japanese Patent Application Publication (JP-A) No. 2019-046796
[0007] PTL 2: JP-A No. 2014-065848
[0008] PTL 3: JP-A No. 2016-149313 SUMMARY OF THE INVENTION
[0010] Technical issues
[0011] In liquid-based batteries, ions are conducted through a liquid electrolyte that has fluidity. In contrast, in all-solid-state batteries, ions are conducted through a solid electrolyte that has no fluidity. In order to form a good ion conduction path, it is preferred to improve the dispersibility (regarding the uniformity and stability of dispersion) of the solid electrolyte.
[0012] The present disclosure has been made in view of the above circumstances, and a main object thereof is to provide an all-solid-state battery including a dispersant-containing layer having good solid electrolyte dispersibility.
[0013] Problem Solution
[0014] To achieve the purpose, the present disclosure provides an all-solid-state battery comprising a cathode layer, an anode layer, and a solid electrolyte layer arranged between the cathode layer and the anode layer, and at least one of the cathode layer, the anode layer, and the solid electrolyte layer is a dispersant-containing layer comprising at least a solid electrolyte and a dispersant, the amine value of the dispersant is greater than 20 mgKOH / g and less than 200 mgKOH / g, the weight-average molecular weight of the dispersant is less than 1,500,000 g / mol, and the proportion of the dispersant in the dispersant-containing layer is greater than 0.1 weight % and less than 20 weight %.
[0015] According to the present disclosure, by using a specific dispersant in a predetermined ratio, an all-solid-state battery including a dispersant-containing layer having good solid electrolyte dispersibility can be obtained.
[0016] In the present disclosure, the weight average molecular weight of the dispersant may be 300 g / mol or more and 150,000 g / mol or less.
[0017] In the present disclosure, the acid value of the dispersant may be 0 mgKOH / g or more and 50 mgKOH / g or less.
[0018] In the present disclosure, the dispersant-containing layer may include aminoamide as a dispersant.
[0019] In the present disclosure, the aminoamide may include at least one of unsaturated polyaminoamide and alkoxyaminoamide.
[0020] In the present disclosure, the dispersant-containing layer may include a polyester-polyamine copolymer as a dispersant.
[0021] In the present disclosure, the cathode layer may be a dispersant-containing layer, and the ratio of the solid electrolyte in the cathode layer may be 10 wt % or more and 30 wt % or less.
[0022] In the present disclosure, the anode layer may be a dispersant-containing layer, and the ratio of the solid electrolyte in the anode layer may be 10 wt % or more and 30 wt % or less.
[0023] In the present disclosure, the solid electrolyte layer may be a dispersant-containing layer, and the ratio of the solid electrolyte in the solid electrolyte layer may be 60 wt % or more.
[0024] The present disclosure also provides a method for preparing the all-solid-state battery described above, and forms the dispersant-containing layer by using a slurry including at least a solid electrolyte and a dispersant.
[0025] According to the present disclosure, by using a slurry including a specific dispersant, an all-solid-state battery including a dispersant-containing layer having good solid electrolyte dispersibility can be obtained.
[0026] Advantageous Effects of the Invention
[0027] The present disclosure demonstrates the effect that an all-solid-state battery includes a dispersant-containing layer having good solid electrolyte dispersibility.
[0028] BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is a schematic cross-sectional diagram illustrating an example of an all-solid-state battery in the present disclosure.
[0030] Figure 2 is a flow chart illustrating an example of a method for preparing an all-solid-state battery in the present disclosure. DETAILED DESCRIPTION
[0031] An all-solid-state battery and a method for preparing the all-solid-state battery in the present disclosure are described in detail below.
[0032] A. All-solid-state battery
[0033] Figure 1 is a schematic cross-sectional diagram illustrating an example of an all-solid-state battery in the present disclosure. Figure 1 The all-solid-state battery 10 shown in the figure includes a cathode layer 1, an anode layer 2, a solid electrolyte layer 3 disposed between the cathode layer 1 and the anode layer 2, a cathode current collector 4 for collecting current of the cathode layer 1, and an anode current collector 5 for collecting current of the anode layer 2. At least one of the cathode layer 1, the anode layer 2, and the solid electrolyte layer 3 is a dispersant-containing layer including at least a solid electrolyte and a dispersant.
[0034] According to the present disclosure, by using a specific dispersant in a predetermined ratio, an all-solid-state battery including a dispersant-containing layer having good solid electrolyte dispersibility can be obtained. For example, in a layer in which the solid electrolyte is locally bonded, the ion conduction path may be insufficient. In particular, when the ion conduction path is insufficient in an electrode layer including an active material, a portion of the active material is isolated, making it impossible to obtain sufficient capacity in some cases. Therefore, it is preferred to improve the dispersibility (regarding the uniformity and stability of the dispersion) of the solid electrolyte.
[0035] In the present disclosure, a specific dispersant is used in a predetermined ratio. As a result, the dispersibility of the solid electrolyte is improved, so that the ion conductivity in the dispersant-containing layer is improved. In addition, by improving the dispersibility of the solid electrolyte in the dispersant-containing layer, the cycle properties are improved.
[0036] 1. Dispersant layer
[0037] The dispersant-containing layer includes at least a solid electrolyte and a dispersant.
[0038] (1) Dispersant
[0039] The dispersant has an amine value. The solid electrolyte generally has an affinity for amines. Therefore, the dispersant with an amine value is adsorbed to the solid electrolyte, and as a result, the dispersibility of the solid electrolyte is improved. The amine value of the dispersant is generally 20 mgKOH / g or more, and may be 30 mgKOH / g or more. When the amine value of the dispersant is too low, the improvement effect of the dispersibility of the solid electrolyte may not be obtained. At the same time, the amine value of the dispersant is generally 200 mgKOH / g or less, and may be 150 mgKOH / g or less. When the amine value of the dispersant is too high, the solubility of the organic solvent (dispersion medium) may be reduced, so that the improvement effect of the dispersibility of the solid electrolyte may not be obtained. In addition, when the amine value of the dispersant is too high, the preparation of the dispersant itself may be difficult. The amine value of the dispersant is specified by measuring according to DIN (Dcutsche Institut fur Normung) 16945. In particular, 0.9 g to 1.3 g of the sample is added to a 200 ml beaker, and 50 ml of glacial acetic acid is added. Then, titration was performed with a 0.1 N HClO4 / acetic acid solution and an automatic potentiometric titrator (Titrator-DL 40 from Mettler Toledo, Ag / AgCl electrode). Then, the amine value was assigned by the following formula.
[0040] Amine value (mgKOH / g) = (ab) × 5.61 / E
[0041] Wherein "a" is the amount (ml) of 0.1N HClO4 required for titration, "b" is the amount (ml) of 0.1N HClO4 required for blank titration, and "E" is the weight (g) of the sample.
[0042] The dispersant may or may not have an acid value, and the former is preferred. That is, the acid value of the dispersant may be greater than 0, or may be 0, and the former is preferred. Solid electrolytes generally have an acid affinity. Therefore, a dispersant with an acid value is adsorbed to the solid electrolyte, so that the dispersibility of the solid electrolyte is improved. Incidentally, it is believed that the amine value is more conducive to the effect of improving dispersibility than the acid value. The acid value of the dispersant is, for example, more than 10 mgKOH / g, and may be more than 20 mgKOH / g. At the same time, the acid value of the dispersant is, for example, less than 150 mgKOH / g, may be less than 100 mgKOH / g, and may be less than 50 mgKOH / g. The acid value of the dispersant is specified by performing a measurement according to DIN EN ISO 2114. In particular, 0.9 g to 1.3 g of a sample is added to an 80 ml beaker, and 50 ml of acetone is added. Then, titration was performed with a 0.1 N NaOH aqueous solution and an automatic potentiometric titrator (Titrator-DL 40 from Mettler Toledo, Ag / AgCl electrode). Then, the acid value was specified by the following formula.
[0043] Acid value (mgKOH / g) = (ab) × 5.61 / E
[0044] Wherein "a" is the amount (ml) of 0.1 N NaOH required for titration, "b" is the amount (ml) of 0.1 N NaOH required for blank titration, and "E" is the weight (g) of the sample.
[0045] The weight average molecular weight of the dispersant is, for example, 200 g / mol or more, 300 g / mol or more, 1,000 g / mol or more, and 1,500 or more. When the weight average molecular weight of the dispersant is too low, the effect of improving the dispersibility of the solid electrolyte may not be obtained. At the same time, the weight average molecular weight of the dispersant is generally less than 150,000 g / mol, may be 150,000 g / mol or less, and may be 100,000 g / mol or less. When the weight average molecular weight of the dispersant is too high, the number of molecules of the dispersant is relatively reduced, so that the effect of improving the dispersibility of the solid electrolyte may not be obtained. Weight average molecular weight (M w ) are designated as polystyrene equivalents based on the GPC method.
[0046] The dispersant includes an amino group in the molecule. The amino group may be -NH2, may be -NHR (R is an element or group other than hydrogen) and may be -NRR' (R and R' are each independently an element or group other than hydrogen). In addition, the dispersant may or may not include an amide bond (-NH-CO-) in the molecule. In addition, the dispersant may or may not include a hydroxyl group (-OH group) in the molecule. In addition, the dispersant may or may not include a branched structure in the molecule.
[0047] The dispersant may be an aminoamide (amine amide). Aminoamide is a compound including an amino group and an amide bond in the molecule. Preferably, the N element in the amino group and the C element in the amide bond are bonded by one or more C elements. Examples of aminoamides may include unsaturated polyaminoamides and alkoxyaminoamides. Unsaturated polyamineamides may be, for example, salts of unsaturated polyamineamides and relatively low molecular weight acidic polyesters. In addition, unsaturated polyamineamides may be, for example, reaction products of tall oil fatty acids with polyethylene glycol, maleic anhydride and unsaturated polyamineamide salts (e.g., reaction products of tall oil fatty acids and diethylenetriamine). Alkoxyaminoamides may be, for example, condensation products of tall oil fatty acids with 2-[(2-aminoethyl)amino]ethanol. Meanwhile, the dispersant may be a polyamine copolymer. Examples of polyamine copolymers may include polyester-polyamine copolymers.
[0048] The proportion of the dispersant in the dispersant-containing layer is generally 0.1% by weight or more, and may be 0.5% by weight or more. When the proportion of the dispersant is too low, the effect of improving the dispersibility of the solid electrolyte may not be obtained. At the same time, the proportion of the dispersant in the dispersant-containing layer is generally 20% by weight or less, may be 15% by weight or less, may be 10% by weight or less, and may be 5% by weight or less. When the proportion of the dispersant is too high, the proportion of the solid electrolyte is relatively reduced, so that the ionic conductivity in the dispersant-containing layer can be reduced. The dispersant-containing layer may include only one type of dispersant, and may include two or more types of dispersants.
[0049] (2) Solid Electrolyte
[0050] The solid electrolyte improves the ion conductivity in the dispersant-containing layer. Examples of the solid electrolyte may include inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and halide solid electrolytes. Among them, sulfide solid electrolytes are preferred for high ion conductivity, and further, for high dispersibility and high affinity.
[0051] Examples of the sulfide solid electrolyte include a solid electrolyte including a Li element, an X element (X is at least one type of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In) and an S element. In addition, the sulfide solid electrolyte may further include any one of an O element and a halogen element. Examples of the halogen element may include a F element, a Cl element, a Br element, and an I element.
[0052] The sulfide solid electrolyte preferably has an anion structure (PS4) in which an ortho-composition is the main component of anions. 3- Structure, SiS4 4- Structure, GeS4 4- Structure, AlS3 3- Structure, and BS3 3- Structure). The reason is that the sulfide solid electrolyte is allowed to have high chemical stability. The ratio of the anion structure of the ortho-composition with respect to the anion structure in the sulfide solid electrolyte is, for example, 70 mol% or more and may be 90 mol% or more. The ratio of the anion structure of the ortho-composition may be determined by methods such as Raman spectroscopy, NMR and XPS. Specific examples of sulfide solid electrolytes may include xLi2S-(lx)P2S5 (x is greater than 0.7 and less than 0.8) and yLi I-zLiBr-(100-yz)Li3PS4 (y is greater than 0 and less than 30, and z is greater than 0 and less than 30).
[0053] The sulfide solid electrolyte may be a glass-based sulfide solid electrolyte, and may be a glass-ceramic-based sulfide solid electrolyte. The glass-based sulfide solid electrolyte may be obtained by vitrifying the raw materials. The glass-ceramic-based sulfide solid electrolyte may be obtained by, for example, heat exchanging the glass-based sulfide solid electrolyte described above. In addition, the sulfide solid electrolyte preferably includes a predetermined crystal structure. Examples of the crystal structure may include a Thio-LISICON type crystal structure, an LGPS type crystal structure, and an Argentum type crystal structure.
[0054] Examples of oxide solid electrolytes may include garnet-type solid electrolytes such as Li7La3Zr2O 12 , perovskite type solid electrolytes such as (Li, La) TiO3 and sodium super ion conductor type solid electrolytes such as Li(Al, Ti)(PO4)3. Examples of nitride solid electrolytes may include Li3N, and examples of halide solid electrolytes may include LiCl, LiI and LiBr.
[0055] Examples of the shape of the solid electrolyte may include a granular shape. The average particle size (D 50 ) is, for example, 0.05 μm or more, and may be 0.1 μm or more. Meanwhile, the average particle size (D 50 ) is, for example, 50 μm or less, and may be 20 μm or less. The average particle size of the solid electrolyte may be calculated by measurement using a laser diffraction type particle size distribution analyzer or a scanning electron microscope (SEM).
[0056] (3) Dispersant layer
[0057] In the present disclosure, at least one of the cathode layer, the anode layer and the solid electrolyte layer is a dispersant-containing layer. In addition, two of the cathode layer, the anode layer and the solid electrolyte layer may be dispersant-containing layers, and all of the cathode layer, the anode layer and the solid electrolyte layer may be dispersant-containing layers.
[0058] 2. Cathode layer
[0059] The cathode layer is a layer including at least a cathode active material, and may further include at least one of a solid electrolyte, a conductive material, a binder, and a dispersant. In addition, the cathode layer may be a dispersant-containing layer described above. In this case, the cathode layer includes at least a cathode active material, a solid electrolyte, and a dispersant.
[0060] Examples of cathode active materials may include oxide active materials. Examples of oxide active materials may include rock salt bed type active materials such as LiCoO2, LiMnO2, LiNiO2, LiVO2, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2; spinel active materials such as LiMn2O4, Li4Ti5O 12 and Li(Ni 0.5 Mn 1.5 )O4; and olivine-type active materials such as LiFePO4, LiMnPO4, LiNiPO4 and LiCoPO4.
[0061] A coating layer including a Li ion conductive oxide may be formed on the surface of the oxide active material. By providing the coating layer, the reaction between the oxide active material and the solid electrolyte (particularly a sulfide solid electrolyte) may be suppressed. Examples of the Li ion conductive oxide may include LiNbO3. The thickness of the coating layer is, for example, 1 nm or more and 30 nm or less.
[0062] Examples of the shape of the cathode active material may include a granular shape. The average particle size (D 50 ) is, for example, 10 nm or more, and may be 100 nm or more. Meanwhile, the average particle size (D 50 ) is, for example, 50 μm or less, and may be 20 μm or less. The average particle size (D 50 ) can be calculated from observations using, for example, a scanning electron microscope (SEM).
[0063] The solid electrolyte and the dispersant may be in the same contents as those described in "1. Dispersant-containing layer" above; therefore, this description is omitted here. The proportion of the solid electrolyte in the cathode layer is, for example, 5% by weight or more, may be 10% by weight or more, and may be 15% by weight or more. When the proportion of the solid electrolyte is too low, a good ion conduction path may not be formed in the cathode layer. At the same time, the proportion of the solid electrolyte in the cathode layer is, for example, 40% by weight or less, may be 30% by weight or less, and may be 25% by weight or less. When the proportion of the solid electrolyte is too high, the proportion of the cathode active material becomes relatively low, so that the energy density of the all-solid-state battery may be low.
[0064] Examples of conductive materials may include carbon materials, metal particles, and conductive polymers. Examples of carbon materials may include granular carbon materials such as acetylene black (AB) and Ketjen black (KB); and fibrous carbon materials such as carbon fibers, carbon nanotubes (CNTs), and carbon nanofibers (CNFs). In addition, examples of adhesives may include fluorine-based adhesives and rubber-based adhesives. The thickness of the cathode layer is, for example, 0.1 μm or more and 1000 μm or less.
[0065] 3. Anode layer
[0066] The anode layer is a layer including at least an anode active material, and may further include at least one of a solid electrolyte, a conductive material, a binder, and a dispersant. In addition, the anode layer may be a dispersant-containing layer described above. In this case, the anode layer includes at least an anode active material, a solid electrolyte, and a dispersant.
[0067] Examples of anode active materials may include metal active materials, carbon active materials, and oxide active materials. Examples of metal active materials may include metal elements and metal alloys. Examples of metal elements included in the metal active materials may include Si, Sn, In, and Al. The metal alloy is preferably a metal alloy including the metal elements described above as main components. Examples of carbon active materials may include intermediate carbon microbeads (MCMB), highly oriented pyrolytic graphite (HOPG), hard carbon, and soft carbon. Examples of oxide active materials may include lithium titanate such as Li4Ti5O 12 .
[0068] The solid electrolyte and the dispersant may be in the same contents as those described in "1. Dispersant-containing layer" above; therefore, this description is omitted here. The proportion of the solid electrolyte in the anode layer is, for example, 5% by weight or more, may be 10% by weight or more, and may be 15% by weight or more. When the proportion of the solid electrolyte is too low, a good ion conduction path may not be formed in the anode layer. At the same time, the proportion of the solid electrolyte in the anode layer is, for example, 40% by weight or less, may be 30% by weight or less, and may be 25% by weight or less. When the proportion of the solid electrolyte is too high, the proportion of the anode active material becomes relatively low, so that the energy density of the all-solid-state battery may be low.
[0069] The conductive material and the binder may be in the same contents as those described in "2. Cathode layer" above; therefore, the description is omitted here. The thickness of the anode layer is, for example, 0.1 μm or more and 1000 μm or less.
[0070] 4. Solid electrolyte layer
[0071] The solid electrolyte layer is a layer disposed between the cathode layer and the anode layer and includes at least a solid electrolyte. The solid electrolyte layer may also include at least one of a binder and a dispersant. In addition, the solid electrolyte layer may be the dispersant-containing layer described above.
[0072] The solid electrolyte, dispersant, and binder used for the solid electrolyte layer may be the same contents as those described in "1. Dispersant-containing layer" and "2. Cathode layer" above; therefore, the description is omitted here. In addition, the proportion of the solid electrolyte in the solid electrolyte layer is not particularly limited, and is, for example, 60% by weight or more, may be 80% by weight or more, and may be 95% by weight or more. At the same time, the proportion of the solid electrolyte in the solid electrolyte layer may be 100% by weight, and may be less than 100% by weight. The thickness of the solid electrolyte layer is, for example, 0.1 μm or more and 1000 μm or less.
[0073] 5. All-solid-state batteries
[0074] The all-solid-state battery in the present disclosure preferably includes a cathode current collector for collecting the current of the cathode layer and an anode current collector for collecting the current of the anode layer. Examples of cathode current collector materials may include SUS, aluminum, nickel, iron, titanium and carbon. Meanwhile, examples of anode current collector materials may include SUS, copper, nickel and carbon.
[0075] All solid-state batteries in the present disclosure may also include a confining fixture that applies a confining pressure to the cathode layer, the solid electrolyte layer, and the anode layer along the thickness direction. The confining pressure is, for example, above 0.1 MPa, may be above 1 MPa, and may be above 5 MPa. By applying a confining pressure, the ionic conductivity and electronic conductivity in the all-solid-state battery are improved. At the same time, the confining pressure is, for example, below 100 MPa, may be below 50 MPa, and may be below 20 MPa. When the confining pressure is too high, the confining fixture may be increased in size.
[0076] The type of the all-solid-state battery in the present disclosure is not particularly limited, and is generally a lithium-ion battery. In addition, the all-solid-state battery in the present disclosure may be a primary battery, and may be a secondary battery. In the above content, the secondary battery is preferred, so as to repeat charging and discharging, and can be used as, for example, a car-mounted battery. In addition, the all-solid-state battery in the present disclosure may be a single-cell battery, and may be a stacked battery. The stacked battery may be a monopolar stacked battery (stacked battery connected in parallel), and may be a bipolar stacked battery (stacked battery connected in series). Examples of the shape of the all-solid-state battery may include a coin-shaped, laminated, cylindrical, and square.
[0077] B. Method for preparing all-solid-state batteries
[0078] Figure 2 is a flow chart illustrating an example of a method for preparing an all-solid-state battery in the present disclosure. Figure 2It is shown in the figure that the method for preparing an all-solid-state battery preferably includes a cathode layer forming step of forming a cathode layer, an anode layer forming step of forming an anode layer, a solid electrolyte layer forming step of forming a solid electrolyte layer, and a pressing step of sequentially placing the cathode layer, the solid electrolyte layer and the anode layer and pressing. In particular, in the present disclosure, at least one of the cathode layer, the anode layer and the solid electrolyte layer is a dispersant-containing layer, and the dispersant-containing layer is formed by using a slurry including at least a solid electrolyte and a dispersant.
[0079] According to the present disclosure, by using a slurry including a specific dispersant, an all-solid-state battery including a dispersant-containing layer having good solid electrolyte dispersibility can be obtained.
[0080] Examples of a method for forming a dispersant-containing layer may include a method including: a coating process of forming a coating layer by coating a substrate with a slurry including at least a solid electrolyte and a dispersant, and a drying process of forming a dispersant-containing layer by drying the coating layer.
[0081] The slurry used for coating treatment includes at least a solid electrolyte and a dispersant. When the dispersant-containing layer is a cathode layer, the slurry also includes a cathode active material. Similarly, when the dispersant-containing layer is an anode layer, the slurry also includes an anode active material. In addition, the slurry may also include at least one of a conductive material and a binder as required.
[0082] The dispersion medium used for the slurry is not particularly limited, and examples may include ketone compounds such as methyl ethyl ketone, diethyl ketone, methyl propyl ketone, methyl isobutyl ketone, dibutyl ketone, and diisobutyl ketone; ether compounds such as diethylene glycol diethyl ether, cyclopentyl methyl ether, dibutyl ether, diamyl ether, and anisole; ester compounds such as ethyl butyrate, butyl butyrate, and 2-methylbutyrate. Ketone compounds, ether compounds, and ester compounds may or may not include a cyclic structure, and the latter is preferred for lower reactivity with a solid electrolyte (particularly a sulfide solid electrolyte).
[0083] There is no particular limitation on the method for preparing the slurry. For high dispersibility of the solid electrolyte, it is preferred that, for example, a first solution is prepared by dissolving a dispersant into a dispersion medium, and then the solid electrolyte is added to and dispersed in the first solution. In addition, when preparing a slurry including other materials such as an active material, a conductive material, and a binder other than a solid electrolyte and a dispersant, it is preferred to prepare the first dispersion by adding a solid electrolyte to the first solution, and then adding other materials. That is, for high dispersibility of the solid electrolyte, it is preferred to add only the solid electrolyte to the first solution.
[0084] Examples of the dispersion method may include methods using common apparatuses such as a dissolver, a homomixer, a kneader, a roll mill, a sand mill, an attritor, a ball mill, a vibration mill, a high-speed impeller mill, an ultrasonic homogenizer, and an oscillator.
[0085] Examples of substrates for coating treatment may include current collectors and transfer sheets. Examples of transfer sheets may include resin sheets such as fluorine-based resin sheets and metal sheets. Examples of methods for coating slurry may include common methods such as scraper methods, die coating methods, gravure coating methods, spray coating methods, electrostatic coating methods, and rod coating methods.
[0086] The drying temperature in the drying treatment is, for example, 60°C or more, 80°C or more, and 100°C or more. Meanwhile, the drying temperature is, for example, 220°C or less, 200°C or less, 170°C or less, and 160°C or less. Examples of methods for drying the coating may include common methods such as warm air drying, infrared drying, reduced pressure drying, and medium heat drying. Examples of drying atmospheres may include inert gas atmospheres such as Ar atmospheres and nitrogen atmospheres. In addition, drying may be performed under atmospheric pressure, and may be dried under reduced pressure.
[0087] Incidentally, the present disclosure is not limited to these embodiments. The embodiments are examples, and any other changes are intended to be included in the technical scope of the present disclosure as long as they have substantially the same configuration as the technical concept described in the claims of the present disclosure and provide similar actions and effects.
[0088] Example
[0089] Example 1
[0090] <Preparation of cathode structure>
[0091] Weigh the following: 64.4 parts by weight of cathode active material (LiNi coated with LiNbO3) 1 / 3 Mn 1 / 3 Co 1 / 3 O2), 27.6 parts by weight of sulfide solid electrolyte (Li I-Li2O-Li2S-P2S5), 3 parts by weight of conductive material (vapor-grown carbon fiber), PVDF binder solution with a solid content of 4 parts by weight and 1 part by weight of dispersant (unsaturated polyaminoamide, A1). Incidentally, the weight ratio of cathode active material and sulfide solid electrolyte is cathode active material: sulfide solid electrolyte = 70:30.
[0092] Next, methyl isobutyl ketone was prepared, and a weighed dispersant was added and dissolved. After confirming the dissolution of the dispersant, the weighed sulfide solid electrolyte was added and dispersed by using an ultrasonic homogenizer (UH-50 manufactured by SMT Co., Ltd.) for one minute. Then, other weighed materials (cathode active material, binder and conductive material) were added, and in addition, methyl isobutyl ketone was added so that the solid content was 60 weight %. The slurry was obtained by dispersing the obtained mixture by using an ultrasonic homogenizer for one minute.
[0093] Thereafter, the surface of the cathode current collector (aluminum foil) was coated with the slurry by using an applicator, naturally dried for 5 minutes, and hot-air dried for 60 minutes at 100° C. Thus, a cathode structure including a cathode current collector and a cathode layer was obtained.
[0094] <Preparation of anode structure>
[0095] Weigh the following: 67.2 parts by weight of anode active material (natural graphite, D 50 =15μm), 28.8 parts by weight of sulfide solid electrolyte (LiI-Li2O-Li2S-P2S5) and PVDF binder solution so that the solid content is 4 parts by weight. Incidentally, the weight ratio of the anode active material and the sulfide solid electrolyte is anode active material: sulfide solid electrolyte = 70:30.
[0096] Next, methyl isobutyl ketone was prepared, and the weighed sulfide solid electrolyte was added and dispersed by using an ultrasonic homogenizer (UH-50 manufactured by SMT Co., Ltd.) for one minute. Then, other weighed materials (anode active material and binder) were added, and further, methyl isobutyl ketone was added so that the solid content was 55% by weight. Slurry was obtained by dispersing the obtained mixture by using an ultrasonic homogenizer for one minute.
[0097] Thereafter, the surface of the anode current collector (SUS foil) was coated with the slurry by using an applicator, naturally dried for 5 minutes, and hot-air dried for 60 minutes at 100° C. Thus, an anode structure including an anode current collector and an anode layer was obtained.
[0098] <Preparation of Solid Electrolyte Layer>
[0099] The following were weighed: 96 parts by weight of a sulfide solid electrolyte (LiI-Li2O-Li2S-P2S5) and a PVDF binder solution so that the solid content was 4 parts by weight. These were mixed, and methyl isobutyl ketone was added so that the solid content was 45% by weight. The obtained mixture was dispersed using an ultrasonic homogenizer for one minute to obtain a slurry.
[0100] Thereafter, the surface of a substrate (aluminum foil) was coated with the slurry using an applicator, naturally dried for 5 minutes, and hot-air dried for 30 minutes at 100° C. Thus, a solid electrolyte layer was obtained on the substrate.
[0101] <Preparation of all-solid-state batteries>
[0102] The substrate was peeled off from the solid electrolyte layer in an inert gas atmosphere, the cathode structure was placed on one surface of the solid electrolyte layer, and the anode structure was placed on the other surface of the solid electrolyte layer. An all-solid-state battery was obtained by pressing the obtained stack at 4.3 tons.
[0103] Examples 2 to 11
[0104] The all-solid-state battery was obtained in the same manner as in Example 1, except that the type and ratio of the dispersant in the cathode layer were changed as shown in Tables 1 and 2. Incidentally, in Tables 1 to 4, CA represents the cathode layer, SE represents the solid electrolyte layer, and AN represents the anode layer. In addition, as for the type of the dispersant, Group A represents unsaturated polyaminoamide, Group B represents alkoxyaminoamide, and Group C represents polyester-polyamine copolymer.
[0105] Example 12
[0106] <Preparation of cathode structure>
[0107] The cathode structure was obtained in the same manner as in Example 1, except that no dispersant was used and the following were used: 65.1 parts by weight of the cathode active material (LiNi coated with LiNbO3) 1 / 3 Mn 1 / 3 Co 1 / 3 O2), 27.9 parts by weight of a sulfide solid electrolyte (LiI-Li2O-Li2S-P2S5), 3 parts by weight of a conductive material (vapor-grown carbon fiber), and a PVDF binder solution so that the solid content is 4 parts by weight.
[0108] <Preparation of anode structure>
[0109] Weigh the following: 66.5 parts by weight of anode active material (natural graphite, D 50 =15μm), 28.5 parts by weight of sulfide solid electrolyte (Li I-Li2O-Li2S-P2S5), PVDF binder solution with a solid content of 4 parts by weight and 1 part by weight of dispersant (unsaturated polyaminoamide, A1). Incidentally, the weight ratio of the anode active material and the sulfide solid electrolyte is anode active material: sulfide solid electrolyte = 70:30.
[0110] Next, methyl isobutyl ketone is prepared, and the weighed dispersant is added and dissolved. After confirming the dissolution of the dispersant, the weighed sulfide solid electrolyte is added and dispersed by using an ultrasonic homogenizer (UH-50 manufactured by SMT Co., Ltd.) for one minute. Then, other weighed materials (anode active material and binder) are added, and in addition, methyl isobutyl ketone is added so that the solid content is 55 weight %. The obtained mixture is dispersed by using an ultrasonic homogenizer for one minute to obtain a slurry. The anode structure is obtained in the same manner as in Example 1, but the difference is that the slurry obtained is used.
[0111] <Preparation of Solid Electrolyte Layer>
[0112] In the same manner as in Example 1, a solid electrolyte layer was obtained.
[0113] <Preparation of all-solid-state batteries>
[0114] An all-solid-state battery was obtained in the same manner as in Example 1, except that the obtained cathode structure, anode structure and solid electrolyte layer were used.
[0115] Example 13
[0116] Initially, a cathode structure (a cathode structure excluding a dispersant) was obtained in the same manner as in Example 12. Then, an anode structure (anode structure excluding a dispersant) was obtained in the same manner as in Example 1. Then, the following was weighed: 93 parts by weight of a sulfide solid electrolyte (Li I-Li2O-Li2S-P2S5), a PVDF binder solution having a solid content of 4 parts by weight, and 3 parts by weight of a dispersant (unsaturated polyaminoamide, A1). These were mixed, and methyl isobutyl ketone was added so that the solid content was 45% by weight. A slurry was obtained by dispersing the obtained mixture for one minute using an ultrasonic homogenizer. A solid electrolyte layer was obtained in the same manner as in Example 1, but the difference was that the obtained slurry was used. An all-solid-state battery was obtained in the same manner as in Example 1, but the difference was that the obtained cathode structure, anode structure, and solid electrolyte layer were used.
[0117] Embodiment 14
[0118] Initially, a cathode structure (cathode structure including a dispersant) was obtained in the same manner as in Example 1. Then, an anode structure (anode structure including a dispersant) was obtained in the same manner as in Example 12. Then, a solid electrolyte layer (solid electrolyte layer including a dispersant) was obtained in the same manner as in Example 13. An all-solid-state battery was obtained in the same manner as in Example 1, except that the obtained cathode structure, anode structure, and solid electrolyte layer were used.
[0119] Comparative Example 1
[0120] An all-solid-state battery was obtained in the same manner as in Example 1, except that no dispersant was used in the cathode layer and the composition of the slurry for the cathode layer was changed as shown in Table 4.
[0121] Comparative Examples 2 to 6
[0122] An all-solid-state battery was obtained in the same manner as in Example 1, except that the type and proportion of the dispersant in the cathode layer were changed as shown in Table 4.
[0123] "evaluate"
[0124] <Dispersibility>
[0125] The dispersibility of the solid electrolyte was evaluated by using the slurry including the dispersants prepared in Examples 1 to 14 and Comparative Examples 1 to 6. The evaluation of the dispersibility was performed based on JIS 5600-2-5:1999 (ISO 1524:1983) by using a grind meter (0 μm to 100 μm scale).
[0126] A: Less than 10μm...better
[0127] B: 10μm or more and less than 30μm...Good
[0128] C: 30μm or more and less than 70μm... Poor
[0129] D: 70μm or more...worse
[0130] <Resistivity>
[0131] The Li ion resistivity of the all-solid-state batteries obtained in Examples 1 to 14 and Comparative Examples 1 to 6 was determined by the AC impedance method. Solar tron 1260 was used for the measurement, and the measurement conditions were: an applied voltage of 10mV, a measurement frequency range of 0.01MHz to 1MHz at ambient temperature. In addition, when measuring, the all-solid-state battery was adjusted as described below. Initially, in an environment of 25°C±1°C, the all-solid-state battery that had not yet been charged was charged with a constant current with a current value of 0.1C until the voltage at the terminal reached a predetermined voltage, and then the all-solid-state battery was charged with a constant current / constant voltage for one hour, maintaining the voltage at a predetermined voltage. Next, the all-solid-state battery was discharged at a constant current / constant voltage for 10 hours to 4.2V at a current value of 0.2C. Thereafter, in an environment of 25°C±1°C, the all-solid-state battery was charged to 4.0V at a constant current at a current value of 0.2C.
[0132] A: Less than 0.9Ωm...better
[0133] B: 0.9Ωm or more and less than 2.4Ωm... Good
[0134] C: 2.4Ωm or more and less than 5.5Ωm... Poor
[0135] D: 5.5Ωm or above...worse
[0136] <Cyclic Nature>
[0137] The all-solid-state batteries obtained in Examples 1 to 14 and Comparative Examples 1 to 6 were repeatedly charged and discharged (CC charging and discharging) at a constant current in the range of 4.2V to 2.5V. Charging and discharging were performed at a current value of 1.0C in an environment of 25°C ± 1°C. The capacity persistence was calculated by dividing the discharge capacity of the 200th cycle by the discharge capacity of the first cycle. The evaluation criteria for capacity persistence (cycling properties) are shown below.
[0138] A: 90% or more...better
[0139] B: 85% or more and less than 90%... Good
[0140] C: 80% or more and less than 85%... Poor
[0141] D: Less than 80%...worse
[0142] [Table 1]
[0143]
[0144] [Table 2]
[0145]
[0146] [Table 3]
[0147]
[0148] [Table 4]
[0149]
[0150] As shown in Tables 1 to 3, it was confirmed that good dispersibility was obtained in each of Examples 1 to 14. Incidentally, in Example 2, the resistivity and cycle properties were not good, although good dispersibility was obtained. Meanwhile, in Example 3, the dispersibility, resistivity, and cycle properties were all good. The above indicates that the ratio of the dispersant is preferably 15% by weight or less.
[0151] Meanwhile, as shown in Table 4, it was confirmed that good dispersibility was not obtained in each of Comparative Examples 1 to 6. The reason is assumed to be that no dispersant was used in Comparative Example 1. In Comparative Example 2, the reason is assumed to be that the proportion of the dispersant was too low. In Comparative Example 3, the reason is assumed to be that the amine value of the dispersant was too high. In Comparative Examples 4 and 5, the reason is assumed to be that the amine value of the dispersant was too low. In Comparative Example 6, the reason is assumed to be that the weight average molecular weight of the dispersant was too high. In addition, in Comparative Examples 1 to 6, the resistivity and cycle properties were also not good.
[0152] As described above, it was confirmed that by using a specific dispersant in a predetermined ratio, a dispersant-containing layer having good solid electrolyte dispersibility can be obtained.
[0153] Reference numerals list
[0154] 1...Cathode layer
[0155] 2...Anode layer
[0156] 3...Solid electrolyte layer
[0157] 4...Cathode current collector
[0158] 5...Anode current collector
[0159] 10...All-solid-state battery
Claims
1. An all-solid-state battery comprising a cathode layer, an anode layer and a solid electrolyte layer disposed between the cathode layer and the anode layer, and at least one of the cathode layer, the anode layer and the solid electrolyte layer is a dispersant-containing layer including at least a solid electrolyte and a dispersant, Features The dispersant-containing layer comprises aminoamide or polyester-polyamine copolymer as a dispersant, The amine value of the dispersant is 20 mgKOH / g or more and 200 mgKOH / g or less, The weight average molecular weight of the dispersant is less than 1,500,000 g / mol, and The ratio of the dispersant in the dispersant-containing layer is 0.1% by weight or more and 20% by weight or less.
2. The all-solid-state battery according to claim 1, characterized in that The weight average molecular weight of the dispersant is 300 g / mol or more and 150,000 g / mol or less.
3. The all-solid-state battery according to claim 1 or 2, characterized in that The acid value of the dispersant is 0 mgKOH / g or more and 50 mgKOH / g or less.
4. The all-solid-state battery according to claim 1 or 2, characterized in that The aminoamide includes at least one of unsaturated polyaminoamide and alkoxyaminoamide.
5. The all-solid-state battery according to claim 1 or 2, characterized in that The cathode layer is a dispersant-containing layer, and the ratio of the solid electrolyte in the cathode layer is 10 wt % or more and 30 wt % or less.
6. The all-solid-state battery according to claim 1 or 2, characterized in that The anode layer is a dispersant-containing layer, and the ratio of the solid electrolyte in the anode layer is 10 wt % or more and 30 wt % or less.
7. The all-solid-state battery according to claim 1 or 2, characterized in that The solid electrolyte layer is a dispersant-containing layer, and The proportion of the solid electrolyte in the solid electrolyte layer is 60% by weight or more.
8. A method for preparing an all-solid-state battery according to any one of claims 1 to 7, and The dispersant-containing layer is formed by using a slurry including at least a solid electrolyte and a dispersant.
Citation Information
Patent Citations
Dispersant
JP2014065848A
Binder composition for lithium ion secondary battery electrode, slurry composition for lithium ion secondary battery electrode, electrode for lithium ion secondary battery and lithium ion secondary battery
JP2016149313A
Solid electrolyte composition, solid-electrolyte-containing sheet and all-solid-state secondary battery, production method for solid-electrolyte-containing sheet and all-solid-state secondary battery, segmented polymer, and non-aqueous-solvent dispersion of polymer and segmented polymer
CN109526241A
Paste composition, electrode material for secondary batteries, electrode for secondary batteries, and secondary battery
CN111263992A